2016
DOI: 10.19044/esj.2016.v12n34p195
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Growth of South Africa’s Agricultural Exports toWorld Markets

Abstract: The paper assesses the factors influencing South Africa's agricultural export growth to its cardinal destinations between 2001 and 2014. A gravity model was used to present investigation of trade flows that has been validated as a suitable tool in determining export growth. The findings indicate that an improvement in South Africa's and importer's GDP causes an increase in agricultural exports. Distance and political stability have been shown to have no influence on the growth of agricultural exports to its tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…In their work, Potelwa et al (2017) assessed the factors influencing South Africa's agricultural export to its cardinal destination between 2001 and 2014. The authors employed a gravity model to investigate trade flow that has been validated as a suitable tool to determine export growth.…”
Section: Time Series Evidencementioning
confidence: 99%
“…In their work, Potelwa et al (2017) assessed the factors influencing South Africa's agricultural export to its cardinal destination between 2001 and 2014. The authors employed a gravity model to investigate trade flow that has been validated as a suitable tool to determine export growth.…”
Section: Time Series Evidencementioning
confidence: 99%
“…The impact of the foreign agricultural trade to households in South Africa is not perfectly significant as the trends of the foreign agricultural trade discovered in coefficients of the TVAR model are inversely proportional to household income and household consumption in South Africa for both regimes. Even though South Africa has an increased foreign trade in agricultural products since the past decade (Potelwa et al, 2016), this does not mean that households in South Africa have a significant benefit on the products because Rossouw et al (2014) showed any change to the monetary sector affects short-term liquidity in the monetary system, which suddenly has an effect on other rates.…”
Section: Discussionmentioning
confidence: 99%
“…The ndings of some studies indicated a positive effect (Hoque and Yusop 2012;Hadjiyiannis, Heracleous and Tabakis 2016;Potelwa, Lubinga and Ntshangase 2017;Shobande 2019), while others reported an insigni cant or even negative relationship (Greenaway, Morgan and Wright 1999;Jenkins 1997). There are also studies that used single country with their speci c effects and others using cross countries with various organizations fostering economic liberalization.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Hoque and Yusop (2012), using the autoregressive distributed lag (ARDL) testing approach for Bangladesh on the impacts of trade liberalisation on export performance from 1972 to 2005, found that trade openness enhances export growth but growth in GDP plays a very signi cant role in export growth. Likewise, Potelwa et al (2017), employing a gravity model to investigate trade ow and the factors determining South Africa's export to its cardinal destination between 2001 and 2014, found that increase in gross domestic product (GDP) caused an increase in the country's export. Cestepe, Yildirima, and Bahtiyar (2015) used xed effects Least Squares and Generalized Method of Moments estimation technique imbedded in a panel gravity model to investigate the export effects of trade liberalization on 13 Middle East and North African (MENA) countries to 30 trading partners in the Organization for Economic Cooperation and Development (OECD).…”
Section: Empirical Literaturementioning
confidence: 99%